DAMPAK KEGIATAN PRODUKTIF DI TAMBANG PASIR TERHADAP PUTUS SEKOLAH PADA JENJANG SMP - Dimas Sulistyo Sunarto; Agus Purnomo; Siti Malikhah Towaf (Jurnal Pendidikan Ilmu Sosial, 2020)
One type of instant economic activity includes being sand miner and sand transporter in the sand mining area. The purpose of this study is to describe the impact of children's productive activities in the sand mine on dropout rates at the junior high school level in Keduwang Village, Blitar Regency. Respondents of the research data amounted to 38 children who carried out productive activities of sand mining. This study used cross-sectional survey research method with a quantitative approach that were supplemented with qualitative data. The collection technique used questionnaire, observation, and interviews. Data analysis techniques used descriptive data analysis techniques with the odds ratio method. The results indicate that the impact of children's productive activities in sand mining on dropout rates at junior high school level with decrease of children’s interest attending school. The results of odd ratio analysis indicate that the riskiest factor causing children to choose school dropout is productive activities in sand mining do not require special skills. The factor of not requiring special skills is proven to be six times the risk of causing children school dropout. The results provide description of how easy economic access and does not require skills has an impact on children's perceptions of going to school or working. Implications for the results of this research are expected to be a reference for government to pay attention to dropout rates that occur due to the productive activities of children in sand mining.